Plastic waste as pyrolysis feedstock for plastic oil production: A review - Chang, Siu Hua (The Science of the total environment, 2023)
Turning plastic waste into plastic oil by pyrolysis is one of the promising techniques to eradicate plastic waste pollution and accelerate the circular economy of plastic materials. Plastic waste is an attractive pyrolysis feedstock for plastic oil production owing to its favorable chemical properties of proximate analysis, ultimate analysis, and heating value other than its abundant availability. Despite the exponential growth of scientific output from 2015 to 2022, a vast majority of the current review articles cover the pyrolysis of plastic waste into a series of fuels and value-added products, and up-to-date reviews exclusively on plastic oil production from pyrolysis are relatively scarce. In light of this void in the current review articles, this review attempts to provide an up-to-date overview of plastic waste as pyrolysis feedstock for plastic oil production. A particular emphasis is placed on the common types of plastic as primary sources of plastic pollution, the characteristics (proximate analysis, ultimate analysis, hydrogen/carbon ratio, heating value, and degradation temperature) of various plastic wastes and their potential as pyrolysis feedstock, and the pyrolysis systems (reactor type and heating method) and conditions (temperature, heating rate, residence time, pressure, particle size, reaction atmosphere, catalyst and its operation modes, and single and mixed plastic wastes) used in plastic waste pyrolysis for plastic oil production. The characteristics of plastic oil from pyrolysis in terms of physical properties and chemical composition are also outlined and discussed. The major challenges and future prospects for the large-scale production of plastic oil from pyrolysis are also addressed. [Display omitted] •LDPE, HDPE, PP, and PS are more promising than PVC and PET as pyrolysis feedstock.•Low to moderate temperature, heating rate, and residence time favor plastic oil.•Lower pressure, smaller particle size and reactive gas atmosphere favor plastic oil.•Catalysts usually promote better plastic oil quality but do not necessarily yield.•Plastic oil is fit for fossil fuel blending/replacement due to its good properties.